Asupan kalsium, vitamin D, kafein, merokok, indeks massa tubuh dan hubungannya dengan kejadian osteoporosis pada pria di Kecamatan Duren Sawit, Jakarta Timur - Eka Susanti; I Dewa Putu Pramantara; Retno Pangastuti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2009)
Background: Osteoporosis can cause public health problem because both man and woman have high risk factor for osteoporosis. This is related to high morbidity and mortality of man. The increase of elderly population intensifies the frequency of the prevalence of osteoporosis, which limits activities of the patients.Objective: To identify the relationship between calcium, vitamin D, and caffeine intake, smoking, and mass body index with osteoporosis among elderly men.Method: This study was analytical observational which used cross sectional design. Subject of the study were men of 55– 65 years old purposively chosen. The study was carried out at Sub district of Duren Sawit, Jakarta Timur.Result: There was no significant relationship between calcium intake and bone mass density (p > 0.05). There was no significant relationship between vitamin D intake and bone mass density (p > 0.05), smoking and bone mass density (p > 0.05), and caffeine consumption and bone mass density (p > 0.05). There was a significant relationship between body mass index and osteoporosis (p < 0.05).Conclusion: The relationship between calcium and vitamin D intake, smoking, caffeine consumption, and osteoporosis was insignificant. The relationship between body mass index and osteoporosis was significant.